TEKNIK PERMAINAN REONG PADA KESENIAN GENDANG BELEQ DI SANGGAR MALIK GIRANG DESA PAOK MOTONG - Hafiz, Alwan; Markarma, Muh.Ridwan; Kailani, Ashwan; Zaiful; Sapriadi (TAMUMATRA, 2025)
The purpose of this research is to find out how the technique of playing reong in the traditional music of gendang beleq art. The method used in this research is qualitative method. Data collection techniques using observation, interview and documentation techniques. The data analysis technique starts from data collection, data reduction, data analysis, presentation, and finally drawing conclusions. Based on the results of the research conducted that in the reong game there are several techniques used including the first Ngambak technique. This technique is used to play the basic notes on the reong by pressing or hitting hard using a reong beater. Second, the Slow or Beradeng technique . The Beradeng technique is one of the techniques played in creating dynamic variations, especially in setting the tempo and intensity of sound. and the last technique used is the kotekan or betimbalan technique . Kotekan or in the Sasak language in the beleq drum game is called betimbalan or in music theory it is called an interlocking pattern or a complementary pattern between two players